Forms and Strategies of Verbal Bullying on Students Speaking Performance in the Classroom; A Case Study at SMAN 2 Tilamuta Students - Ira Riswana K. Raya; Sartin T. Miolo; Sri Rumiyatiningsih Luwiti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to identify the forms and strategies of verbal bullying that affect the speaking performance of students at SMA N 2 Tilamuta. The method employed is a qualitative approach, utilizing case studies that involve observation, interviews, and document analysis. Data were collected from nine students who experienced verbal bullying. The findings indicate that verbal bullying takes the form of name-calling and hurtful comments about English proficiency. The impact of this bullying included increased anxiety and decreased motivation to learn, which hindered students' ability to speak English. Students employed various strategies to cope with bullying, including focusing on self-development, disregarding negative comments, and seeking social support from friends and teachers. The conclusion of this study highlights the importance of creating a safe and supportive learning environment to enhance students' speaking skills and mitigate verbal bullying. This research provides significant insights for educators and policymakers to develop effective interventions in linguistically diverse educational contexts.